Selenoprotein-P deficiency is associated with higher risk of incident heart failure. (3rd October 2022) - Jujic, A; Molvin, J; Schomburg, L; Struck, J; Bergmann, A; Melander, O; Magnusson, M
Abstract: Background: Selenium deficiency has been associated with all-cause and cardiovascular mortality, incident cardiovascular disease (coronary artery disease, myocardial infarction and stroke), and with poor prognosis in patients with acute heart failure (HF). Furthermore, high selenium levels were recently shown to be associated with reduced mortality and reduced incidence of HF in non-smokers. Purpose: To examine if selenoprotein-P (SELENOP), a main carrier protein of selenium, is associated with incident HF. Methods: SELENOP concentrations were measured in 5060 randomly selected subjects from the population-based prospective cohort study "the Malmö Preventive Project" (n=18240) using a validated ELISA approach. After exclusion of subjects with prevalent HF (n=230), complete data on all co-variates was available in 4803 subjects (1400 women (29.1%), mean age 69.6±6.2 years, 885 (19.7%) current smokers). SELENOP was continously related to risk of incident HF using Cox regression models adjusted for age, sex, body mass index, systolic blood pressure, anti-hypertensive treatment, smoking status, diabetes status, low-density lipoprotein cholesterol levels, and prevalent coronary events. Further, subjects within the lowest SELENOP quintile were compared to subjects in the remaining four quintiles in an adjusted model. Results: Each 1 SD increment in SELENOP levels was associated with lower risk of incident HF (n=436) during a median follow-up period of 14.7 years (interquartile range 10.9–15.7 years, hazard ratio (HR) 0.92, 95% confidence interval (95% CI) 0.84–0.99; p=0.049 in a model adjusted for cardiovascular risk factors. Multivariate quintile analyses revealed that the subjects in the lowest SELENOP quintile were at the highest risk of incident HF in an adjusted model (HR 1.46; 95% CI: 1.17–1.83 for incident HF; p for trend 0.039) illustrated in a Kaplan-Meier survival analysis (Figure 1). No interaction effect was seen for sex or smoking. Conclusion: Low SELENOP levels are associated with a higher risk of incident HF supporting recent studies, which further emphasizes the need for randomly controlled trials to examine if supplementation with selenium improves prognosis. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Swedish Medical Research CouncilSwedish Society of Medicine